A Tale of Two Axolotls. (1st November 2015) - Voss, S. Randal; Woodcock, M. Ryan; Zambrano, Luis
Abstract: The Mexican axolotl (Ambystoma mexicanum) is an icon of culture, a revered aquarium pet, and a highly valued animal model in biomedical research. Unfortunately, Mexican axolotls are critically endangered in their natural Xochimilco habitat in Mexico City. If axolotls go extinct, current efforts to conserve the Xochimilico ecosystem will be undermined, as will efforts to genetically manage the laboratory populations that are needed to sustain research efforts around the world. A concerted global effort is needed to protect and manage this irreplaceable species in natural and laboratory environments.